Prevalence of hypertension and cardiovascular disease risk factors among medical students in Kathmandu Valley, Nepal. - Devkota, Surya (2021)
SUMMARY: Hypertension or high blood pressure is the constant pumping of blood through blood vessels with excessive force and is one of the most important causes of premature death worldwide. A cross sectional study was done among medical students of Kathmandu valley ot assess modifiable risk factors of hypertension. A total of 422 students participated in this study of which 65.16% were out of the total tobacco, smokers users, 79.56% of the respondents were daily tobacco users and 63.9% of the respondents were current smokers. The mean age of initiation of smoking and alcohol was 19.56years and 18.666 years respectively. 44.85% male used to consume alcohol less than one time a month and 16.36% consumed alcohol 1-3 days per month whereas among female, it was found to be 23.64% and 2.42% respectively. 17.95%,48.72% and 33.33% of the respondents were found to involve in high, moderate and low physical activities respectively. Similarly, while travelling to and from places, 43.59%,35.90% and 20.51% were found to involve in high moderate and low physical activities respectively. More evidences must be generated to understand the burden of modifiable risk factors of hypertension, the pattern of its distribution and the risk of developing hypertension in future among medical students.